"Free Speech Is Sometimes a Dangerous Privilege": Western Editors' Support for Press Suppression during the US Civil War. Issue 3 (3rd July 2021) - Cronin, Mary M.
ABSTRACT: Little research has been undertaken that examines editors' views on freedom of the press during wartime. This research explores how and why editors in the far Western states and territories supported, encouraged, and rationalized press suppression during the American Civil War. Despite their distance from the fighting, the majority of the West's Republican editors believed passionately in the Union cause and pledged their loyalty to the nation. Many members of the Democratic press did, as well. But two-party partisan hostilities motivated editors to encourage press suppression, as did fear of the opposition press's power. Economic concerns also proved a motivating factor for press suppression in some communities. Western press members often used popular, rather than Constitutional, definitions of treason to support, explain, and encourage suppression of fellow editors whose newspapers appeared disloyal.